2022
DOI: 10.7759/cureus.21394
|View full text |Cite
|
Sign up to set email alerts
|

Functional Vitamin B12 Deficiency in Association With Nitrous Oxide Inhalation

Abstract: There is a rise in the use and abuse of nitrous oxide (N₂O) as a recreational drug. In spite of the laws enforced internationally, it remains readily available and is an inexpensive mode of recreational drug. Commonly known as the ‘laughing gas’, its use as a euphoric agent is on the rise. Subsequently, the side effects are also coming to light, associated with medical, financial and social implications. It is not detected in routine drug testing. The key differential in an acute setting is often confused with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“… 8 It has also been suggested that there are inhibitory effects on N‐methyl‐d‐asparate receptors in the central nervous system, stimulation of noradrenergic pathways and sympathetic actions via α‐1‐adrenergic stimulation, although these are not well understood. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 8 It has also been suggested that there are inhibitory effects on N‐methyl‐d‐asparate receptors in the central nervous system, stimulation of noradrenergic pathways and sympathetic actions via α‐1‐adrenergic stimulation, although these are not well understood. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…8 noradrenergic pathways and sympathetic actions via α-1-adrenergic stimulation, although these are not well understood. 8,9 Treatments will begin with ceasing N 2 O use and intramuscular vitamin B 12 injections. Approximately 75% of the 96 patients in the review saw either a reduction or complete resolution of neurological systems if they followed this treatment over subsequent weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that vitamin B12 levels are not always low in cases of N 2 O-induced SCD of the spinal cord, as evidenced in a 2016 systematic review by Garkani et al, which reported that B12 levels were only low in 46% of patients with N 2 O-induced neurological symptoms [ 2 ] . This implies that N 2 O can also cause a functional B12 deficiency rather than an absolute depletion [ 3 , 4 ] . If there is suspicion of N 2 O-induced neurological symptoms and vitamin B12 levels are normal, serum levels of methylmalonic acid and homocysteine can be measured instead, which accumulate if B12 is inactive or levels are low [ 1 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B12 deficiency is known to be associated with increased homocysteine levels (hyperhomocysteinemia); vitamin B12 is needed as a cofactor to remethylate homocysteine to methionine. This hyperhomocysteinemia, reported to be associated with neurological symptoms arising from vitamin B12 deficiency (and with nitrous oxide abuse) [ 15 ], can increase the propensity for arterial and venous thrombosis [ 16 ] and therefore has also been reported to be associated with SVT [ 17 ].…”
Section: Discussionmentioning
confidence: 99%